73.4k views
2 votes
(4.3 * 10-3)(2 x 10-2)​

2 Answers

3 votes

✽ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ✽


(4.3\cdot10-3)(2\cdot 10-2)


= (43 - 3)((2) (10) -2)


= 40 ((2) (10)-2)


= 40(20 - 2)


= (40)(18)


= 720

➶ Hope This Helps You!

➶ Good Luck (:

➶ Have A Great Day ^-^

↬ May ♡

User Dzamo Norton
by
4.8k points
3 votes

Given expression:

(4.3 x
10^(-3)) (2 x
10^(-2))

Solving this equation,

(4.3 x
10^(-3)) (2 x
10^(-2)) = 4.3 x
10^(-3) x 2 x
10^(-2)

= (4.3 x 2) x 10⁻³ x 10⁻²

= 8.6 x 10⁻³ ⁺⁽⁻²⁾

= 8.6 x 10⁻⁵

The solution of this problem is 8.6 x 10⁻⁵

User Yolanda
by
4.8k points